Modeling the influential factors for participating in critical reading among undergraduates / Nadia Anuar - Anuar, Nadia (2020)
Critical reading is an essential skill that students must acquire in the completion of tertiary education. Yet, students’ critical reading performance has been reported to be unsatisfactory. Hence, there is an urgent need to identify factors that influence students’ participation in critical reading. Theory of Planned Behaviour was employed to examine the influence of students’ attitude, subjective norm, and perceived behavioural control on students’ intention to participate in critical reading. The influence of students’ behavioural belief, normative belief, and control belief on students’ intention was also investigated. This study also determined the mediating role of attitude, subjective norm, and perceived behaviour control. A quantitative methodology was employed, and the questionnaire was utilised as the instrument. The items in the questionnaire were developed from an elicitation study and adapted from previous studies. The respondents of this study were students from a public university and simple random sampling method was used. The data collected yielded 220 usable questionnaires. Statistical Package for Social Science (SPSS) and Analysis of Moment Structures (AMOS) were used to analyse the data. Attitude, subjective norm, and perceived behaviour control had a significant effect on behavioural intention where subjective norms had the highest influence on behavioural intention. The study has also determined that behavioural belief, normative belief, and control belief influence intention but must pass the mediating variables to exert influence on intention as they have no direct effect on behavioural intention. The mediating results support this as attitude, subjective norm, and perceived behavioural control are revealed to exert full mediation which are reconfirmed by the bootstrapping results. The rigorous methodology has contributed to the development of Reading Intention Questionnaire Protocol (RIQP) which can be utilised for future reading in teaching and learning. A noteworthy finding of this study is that students’ participation in critical reading was identified to increase when encouraged by relevant stakeholders such as parents and teachers. This may be attributed to the collectivist culture in Malaysia. Thus, the findings of this study have significant practical and pedagogical implications in ensuring meaningful teaching and learning.